2022
DOI: 10.3390/ijms23031808
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages/Microglia in Glioblastoma Oncolytic Virotherapy: A Double-Edged Sword

Abstract: Oncolytic virotherapy is a rapidly progressing field that uses oncolytic viruses (OVs) to selectively infect malignant cells and cause an antitumor response through direct oncolysis and stimulation of the immune system. Despite demonstrated pre-clinical efficacy of OVs in many cancer types and some favorable clinical results in glioblastoma (GBM) trials, durable increases in overall survival have remained elusive. Recent evidence has emerged that tumor-associated macrophage/microglia (TAM) involvement is likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 117 publications
0
22
0
Order By: Relevance
“…Before discussing the effect of autophagy on the TME of glioblastoma, it was necessary to clarify the characteristics of immune cell in ltration in glioblastoma. Previous studies have shown that the immune landscape in glioblastoma is dominated by macrophages M2 and plays a crucial role in promoting tumor growth (30,31). We constructed the glioblastoma differentiation trajectory based on the scRNA-seq data from the CGGA database, and cell annotation indicated that the immune components within trajectories were monocytes, macrophages, and T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Before discussing the effect of autophagy on the TME of glioblastoma, it was necessary to clarify the characteristics of immune cell in ltration in glioblastoma. Previous studies have shown that the immune landscape in glioblastoma is dominated by macrophages M2 and plays a crucial role in promoting tumor growth (30,31). We constructed the glioblastoma differentiation trajectory based on the scRNA-seq data from the CGGA database, and cell annotation indicated that the immune components within trajectories were monocytes, macrophages, and T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia specific molecular markers such as TMEM119 and P2RY12 are applicable to distinguish microglia from peripheral macrophages ( van Wageningen et al., 2019 ; Mercurio et al., 2022 ). Despite their differences in ontogeny and spatial distribution, microglia and peripheral macrophages share similar functions in the glioma microenvironment and are referred as single cell cluster, i.e., TAMs ( Blitz et al., 2022 ; Rao et al., 2022 ).…”
Section: Tumor-associated Microglia/macrophagesmentioning
confidence: 99%
“…Furthermore, a nucleic acid nanogel that mimics surface properties of the influenza virus has been used to reprogram microglia and macrophages for GBM therapy [ 211 ]. This is particularly interesting because tumour-associated microglia and macrophages often contribute to the failure of oncolytic virotherapy by preventing an efficient intratumoral viral distribution [ 212 ]. Another study has suggested that engineered microglia can be used to potentiate the action of drugs against glioma [ 213 ].…”
Section: Recent Advances In the Development Of Novel Therapeutic Appr...mentioning
confidence: 99%